Revista de Educação (1921-1923): republican moral and civility in teacher training - Angélica Pall Oriani; Carlos da Fonseca Brandão; Leila Maria Inoue (Universidade Estadual Paulista Júlio de Mesquita Filho, 2014)
In this paper, are analyzed the content of morality and civility disclosed in five articles published in the Revista de Educação, educational periodic published by the School for Teaching Training of Piracicaba, between 1921 and 1923, and that had Lourenço Filho as editor. For the analysis, it was used aspects of the theory of civilization processes, based on the emotional control idea, proposed by the German sociologist Norbert Elias, in the first decades of the twentieth century. Through historical approach, it was founded in these articles the principles of civility and of morality that should be taught through the school to the teaching training students so they could teach it to their students, future citizens of Republic. From the analysis of the articles of this journal it was possible to observe the "drawing" of citizen who was disclosed and, consequently, the spread - through the school - of values related to social behavior that matched to the standards of civilized individuals to the Brazilian Republic.